Technology agreements with heterogeneous countries - Michael Hoel; Aart de Zeeuw (Fondazione Eni Enrico Mattei (FEEM), 2013)
For sufficiently low abatement costs many countries might undertake significant emission reductions even without any international agreement on emission reductions. We consider a situation where a coalition of countries does not cooperate on emission reductions but cooperates on the development of new, climate friendly technologies that reduce the costs of abatement. The equilibrium size of such a coalition, as well as equilibrium emissions, depends on the distribution across countries of their willingness to pay for emission reductions. Increased willingness to pay for emissions reductions for any group of countries will reduce (or leave unchanged) the equilibrium coalition size. However, the effect of such an increase in aggregate willingness to pay on equilibrium emissions is ambiguous.
Keywords: F42; O32; Q2; C72; 330; Technology Agreement; Coalition Stability; Climate; International Agreement